Spatial distribution and ecological risk of heavy metal in surface sediment of Old Brahmaputra River, Bangladesh. Issue 2 (7th February 2023) - Islam, Md. Sirajul; Shammi, Rifat Shahid; Jannat, Rahiatul; Kabir, Md. Humayun; Islam, Md. Saiful
ABSTRACT: The study was conducted to investigate the concentrations, distributions, sources, and potential ecological risk of heavy metals in surface sediments from the Old Brahmaputra River. Sediment samples were collected from five sampling stations and analyzed with an inductively coupled plasma mass spectrometer (ICP-MS). The results showed that mean concentrations (mg/kg) of heavy metals were in order of Ni (58.82) > Cr (32.45) > Pb (21.04) > Cu (14.24) > Cd (3.81) > As (2.02). Element-specific environmental indices exposed that the ecological risks trailed in the same downward direction as Cd > Ni > Pb > As > Cu > Cr. The contamination factor (CF), enrichment factor (EF), and geo-accumulation index (Igeo) exposed all cases to a modest level of contamination except for Cd, which has a significant level of contamination. Only Ni and Cd were found to pose a high ecological risk for aquatic life based on the sediment quality guidelines. The prospective ecological risk factor and potential ecological risk both suggested low to moderate ecological risk. The river sediments were mostly uncontaminated or mildly contaminated, posing a minimal ecological risk. The study concluded that the Old Brahmaputra River is subjected to anthropogenic disturbances in its aquatic environment.